DISMISSAL FOR DUE CAUSE IN CASE OF CHEMICAL DEPENDENCY: AN ETHICAL AND LEGAL ISSUE (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
This paper discusses the legal, ethical, and social aspects of dismissal for due cause of workersin situations of chemical dependency. Recognized as a disease by the OMS, chemicaldependency requires an approach that goes beyond punishment, taking into account social,cultural, and public health factors. The application of Article 482 of the CLT is analyzed,especially regarding habitual intoxication or intoxication at work, in light of the FederalConstitution, highlighting that the Superior Labor Court (TST) and the 2nd Regional LaborCourt (TRT-2) have acknowledged that dismissals motivated solely by addiction, without prioroffer of treatment or support, may be considered discriminatory and null. It is concluded thatdismissal for cause in such cases should not be the first measure taken, and principles such ashuman dignity, the right to health, and social reintegration should prevail, reinforcing theresponsibility of companies to adopt a humanized and inclusive approach.